Phenylalanine modulates casein synthesis in bovine mammary epithelial cells by influencing amino acid transport and protein synthesis pathways - Yuanyuan Xing; Yuanyuan Xing; Yuanyuan Xing; Yixuan Luo; Yixuan Luo; Mei Sun; Mei Sun; Jing Yang; Jing Yang; Shaoxiong Lin; Shaoxiong Lin; Xiaojia Mu; et al. (Frontiers in Nutrition, 2025)
The efficiency of phenylalanine (Phe) utilization for milk protein synthesis in dairy cows is limited, and its uptake and metabolic mechanisms in the mammary tissue remaining unclear. This study investigated the effects of Phe availability (0.07, 0.14, 0.28, and 0.56 mM) on amino acid metabolism and casein synthesis in bovine mammary epithelial cells (BMECs) cultured for 24 h. Results showed that αS1-casein, β-casein, and κ-casein expression peaked at 0.14 mM Phe (p < 0.05). At this optimal concentration, amino acid transporters (SLC7A5, SLC7A8, and SLC38A2) were upregulated, corresponding with enhanced uptake of Met, Ile, His, and Arg (p < 0.05). The mammalian target of rapamycin (mTOR) signaling pathway was activated as evidenced by increased phosphorylation of P70 S6 kinase (P70S6K) and mTOR (p < 0.05), while the general control nonderepressible 2 (GCN2) pathway was suppressed through reduced eukaryotic initiation factor 2α (eIF2α) phosphorylation (p < 0.05). As Phe concentration increased, its net uptake increased linearly (Plinear < 0.05) while uptake efficiency decreased linearly (Plinear < 0.05). High Phe concentration (0.56 mM) inhibited amino acid transporter expression and reduced uptake of Leu, Pro, and Tyr (p < 0.05). Additionally, Phe-to-Tyr conversion was dynamically regulated, with phenylalanine hydroxylase (PAH) activity inhibited at 0.07 mM Phe (p < 0.05) but enhanced at higher concentrations, concurrent with reduced exogenous Tyr uptake (p < 0.05). These findings show that casein synthesis in BMECs is optimal at 0.14 mM Phe, coinciding with enhanced expression of amino acid transporters and activation of protein synthesis pathways. In contrast, higher Phe concentrations (0.56 mM) are associated with reduced amino acid utilization efficiency. These observations suggest potential mechanisms by which Phe concentration may regulate milk protein synthesis in dairy cows.